(untitled) (Journal of Atomic and Molecular Sciences, 2021)
The transverse Stark shift of the electronic energy levels in GaAs semiconducting quantum box is investigated by the use of variational solutions to the effective-mass approximation. It is found an interesting phenomenon that the largest Stark shift is obtained for the electric field directed along the diagonal in cross section of a quantum box, while for a rectangular one, the shift reaches peak value for the low field directed along a side of cross section and for the high field along the diagonal. Likewise, the conclusion is shown that the transverse Stark shift in a quantum box depends highly on the ratio of cross sectional sides while is irrelevant to its height. The large Stark shift of the electron and hole trapped in a quantum box leads to an obvious reduction of the interband recombination and wide irradiance spectrum.